In search of the lost legend or ‘the missing’ in landscapes: nationalism, propaganda and ideology in Kuvâyi Milliye and Memleketimden İnsan Manzaraları - Irmak, İ. Erkan. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
Kuvâyi Milliye and Memleketimden Đnsan Manzaraları are probably two of the most famous texts of Turkish Literature, both written by Nâzım Hikmet in Bursa prison during the 1940s. In addition to their literary quality, the importance of these texts derives mainly from Nâzım Hikmet’s ideological stance: communism which is still regarded as a taboo as well as a sign of treason by most people. In this respect, both texts have been utilized by the adherents of various mainstream ideologies, such as Kemalism, nationalism, Islamism, and socialism, for their respective political objectives particularly to prove that Nâzım Hikmet is either a patriot or a traitor. Besides their ideological manipulation, another interesting characteristic of Kuvâyi Milliye and Memleketimden İnsan Manzaraları occurs in their writing, publishing, and reception processes, which intertwine and intermingle with one another. This thesis focuses primarily on the literary history of Kuvâyi Milliye and Memleketimden İnsan Manzaraları in order to show how nationalism, propaganda, and ideology shape their writing process and content. This thesis also argues the importance of generic and narratological characteristics of Kuvâyi Milliye and Memleketimden İnsan Manzaraları in this process of re-writing and contends that these texts are antithesis of each other, especially in the interpretation of the official history, regime, and discourse of Turkey.